2009
DOI: 10.1007/s00049-009-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Detecting pigments from colourful eggshells of extinct birds

Abstract: The known chemical basis of diverse avian eggshell coloration is generated by the same two classes of tetrapyrrole pigments in most living birds. We aimed to extend the evolutionary scope of these patterns by detecting pigments from extinct birds' eggs. In our samples biliverdin was successfully extracted from subfossil shell fragments of the blue-green egg-laying upland moa Megalapteryx didinus, while protoporphyrin was extracted from the beige eggs of two other extinct moa species. Our data on pigment detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…The pigment in two blue eggshell fragments from upland moa Megalapteryx didinus had previously been identified as biliverdin using destructive techniques (Igic et al, 2010). Here, we also identified biliverdin in upland moa eggshell fragments with nondestructive Raman spectroscopy (Fig.…”
Section: Case Study 2: Pigment Detection In Extinct Moa Eggshellssupporting
confidence: 66%
See 3 more Smart Citations
“…The pigment in two blue eggshell fragments from upland moa Megalapteryx didinus had previously been identified as biliverdin using destructive techniques (Igic et al, 2010). Here, we also identified biliverdin in upland moa eggshell fragments with nondestructive Raman spectroscopy (Fig.…”
Section: Case Study 2: Pigment Detection In Extinct Moa Eggshellssupporting
confidence: 66%
“…Sulphuric acid extraction of eggshell pigments and subsequent mass spectrometry were performed on eggshell fragments from domestic chicken, emu, elegant crested tinamou, great tinamou and Japanese quail, following protocols described in Igic et al (2010). Eggshell samples were acquired as above, but were not the same eggshells used for Raman spectroscopy.…”
Section: Mass Spectrometry: Samples Instrumentation and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Igic et al (2010) found that the pigment biliverdin is responsible for the blue-green colour in shell fragments of M. didinus, while protoporphyrin was found in the beige eggs of two other moa species.…”
Section: Moa Breeding: Nests and Eggsmentioning
confidence: 97%